Manganese (II) Complex of 1,4,7-Triazacyclononane-1,4,7-Triacetic Acid (NOTA) as a Hepatobiliary MRI Contrast Agent - Md. Kamrul Islam; Ah-Rum Baek; Byeong-Woo Yang; Soyeon Kim; Dong Wook Hwang; Sung-Wook Nam; Gang-Ho Lee; Yongmin Chang (MDPI AG, 2023)
Magnetic resonance imaging (MRI) is increasingly used to diagnose focal and diffuse liver disorders. Despite their enhanced efficacy, liver-targeted gadolinium-based contrast agents (GBCAs) raise safety concerns owing to the release of toxic Gd3+ ions. A π-conjugated macrocyclic chelate, Mn-NOTA-NP, was designed and synthesized as a non-gadolinium alternative for liver-specific MRI. Mn-NOTA-NP exhibits an r1 relaxivity of 3.57 mM−1 s−1 in water and 9.01 mM−1 s−1 in saline containing human serum albumin at 3 T, which is significantly greater than the clinically utilized Mn2+-based hepatobiliary drug, Mn-DPDP (1.50 mM−1 s−1), and comparable with that of GBCAs. Furthermore, the in vivo biodistribution and MRI enhancement patterns of Mn-NOTA-NP were similar to those of the Gd3+-based hepatobiliary agent, Gd-DTPA-EOB. Additionally, a 0.05 mmol/kg dose of Mn-NOTA-NP facilitated high-sensitivity tumor detection with tumor signal enhancement in a liver tumor model. Ligand-docking simulations further indicated that Mn-NOTA-NP differed from other hepatobiliary agents in their interactions with several transporter systems. Collectively, we demonstrated that Mn-NOTA-NP could be a new liver-specific MRI contrast agent.